USE OF INNOVATIVE METHODS IN THE DEVELOPMENT OF PROFESSIONAL SKILLS OF STUDENTS - G . Rizamukhamedov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Vocational training is a complex and multifaceted process, which integrates opportunities for successful work in a particular profession, personal orientation, professional knowledge, skills, qualifications and professional qualities, work experience. The effectiveness of innovative methods and technologies in its formation today is great. The knowledge and skills of students are developed through the use of innovative methods in the educational process in order to improve the professional skills of students. In this article, I want to emphasize the role of innovative methods and the importance of modern technologies in professional development.